Development of Augmented Reality Media Based on Assembler Edu on Molecular Geometry - Achmad Rante Suparman; Murtihapsari Murtihapsari; Besse Firanita Astari; Ramlah Ramlah; Faisal Faisal (Universitas Lambung Mangkurat, 2025)
This study aimed to develop and evaluate the effectiveness of Augmented Reality (AR)-based learning media using Assembler Edu to enhance the understanding of molecular geometry concepts at the Senior High School (SMA) level. The research employed a Research and Development (R&D) approach, incorporating both the Spiral and Waterfall development models. These models consisted of four main stages: setting objectives, identifying and mitigating risks, designing, and developing. Data were collected through expert validation, student trials, and user satisfaction questionnaires. Five validators assessed the media, and its validity was analyzed using Aiken’s V formula, while reliability was measured through inter-rater agreement. The results showed that all Aiken’s V values were above 0.8, indicating strong agreement among experts and confirming the validity across all categories. The inter-rater agreement values exceeded 75% (kappa > 0.70), demonstrating a high level of consistency among validators. Trials were conducted with 60 students from two schools: MAN 1 Prafi Manokwari and SMA 3 Kendari. The findings indicated a low difficulty level and reflected positive student responses toward the use of AR media for learning molecular structures. In conclusion, this study demonstrated that AR-based learning media offers an innovative and effective solution for enhancing chemistry education.